Efficacy and Safety of Miebo® (Perfluorohexyloctane Ophthalmic Solution) in Treating Dry Eye Disease - a narrative review - Nowoświat, Patrycja; Kozicz, Michał Andrzej; Cuper, Paulina; Jastrzębska, Ilona; Bilecki, Krzysztof; Gugulski, Hubert; Bado, Michał; Mrowczyk, Patrycja (Quality in Sport, 2024)
Introduction: Dry eye disease (DED) is a prevalent and debilitating ocular condition characterized by discomfort, visual disturbances, and tear film instability. Recent therapeutic developments have introduced perfluorohexyloctane ophthalmic solution (Miebo®) as a potential treatment for DED, particularly in patients with meibomian gland dysfunction (MGD). Aim of the Study: This narrative review aims to evaluate the efficacy and safety of Miebo® in treating DED based on current clinical evidence. Materials and Methods: A comprehensive literature search was conducted in PubMed, Embase, and Cochrane Library databases up to May 2024 resulting in the identification of 9 studies. The review included randomized controlled trials, prospective cohort studies, and systematic reviews that focused on the use of Miebo® for DED. Data on efficacy in improving tear film stability and symptom relief, as well as safety profiles, were extracted and analyzed. Results: The evidence indicates that Miebo® significantly enhances tear film stability and alleviates symptoms of DED, with pronounced benefits observed in patients with MGD. Comparative studies demonstrate that Miebo® is more effective than conventional treatments, such as artificial tears and lipid-based formulations. Safety assessments reveal minimal ocular surface discomfort and no significant systemic adverse events associated with Miebo® use. Conclusion: Miebo® shows substantial efficacy and a favorable safety profile in managing DED, making it a valuable therapeutic option, particularly for patients who do not respond to traditional therapies. However, further research is needed to confirm its long-term effectiveness and safety.